The potential and perception of sawah lukis ecotourism - Selfira, Selfira; Prahmana, I Gusti (Junal Ilmu Manajemen, 2024)
The aim of this research is to determine public perceptions and the potential that exists in Sawah Lukis ecotourism. The population of the research is the local community. The research sample used Purposive Random Sampling technique with a total of 55 people. Data collection methods are carried out in several ways, namely observation, in-depth interviews, and questionnaires. The data was then analyzed using qualitative descriptive analysis methods. Based on the results of observations and interviews, Sawah Lukis ecotourism actually has economic value and the potential for further development. For the sustainability of the existence of ecotourism, institutional-based promotional activities and collaboration are needed to improve the quality of promotion.